To shunt or not to shunt in combined orthopedic and vascular extremity trauma. Issue 6 (December 2018) - Wlodarczyk, Jordan R.; Thomas, Alexander S.; Schroll, Rebecca; Campion, Eric M.; Croyle, Caroline; Menaker, Jay; Bradley, Matthew; Harvin, John A.; Collum, Morgan L.; Cho, Jayin; Seamon, Mark J.; Leonard, Jennifer; et al.
Abstract : BACKGROUND: There exists a long established but not validated practice of placing temporary intravascular shunts (TIVS) in cases of combined vascular and orthopedic extremity trauma. Though logical to prioritize blood flow, large-scale data to support this practice is lacking. We hypothesize that the order of repair yields no difference in outcomes in combined vascular and orthopedic extremity trauma and offer a larger-scale analysis than is previously available. METHODS: A retrospective chart review was conducted at six Level I trauma centers from 2004 to 2015 comparing patients who received a TIVS during their initial surgery versus those who did not. Nonshunted patients were further divided into initial definitive vascular repair versus initial orthopedic fixation groups. Metrics were used to control for sampling bias while revision rate, amputation, hospital length of stay (HLOS), and development of thrombosis and compartment syndrome were used to assess outcomes. RESULTS: Of 291 total patients, 72 had TIVS placement, 97 had initial definitive vascular repair, and 122 had initial orthopedic fixation. The shunted group had a higher Abbreviated Injury Scale (3.0 vs. 2.8 p = 0.04) and Mangled Extremity Severity Score (6.1 vs. 5.7 p = 0.006) and a significantly lower rate of compartment syndrome (15% vs. 34% p = 0.002). Among patients who developed compartment syndrome, those who were shunted were younger (23 vs. 35 yrs, p = 0.03) and were more likely sustain a penetrating injury ( p = 0.007). Those receiving initial orthopedic fixation had a longer HLOS (HLOS >15 days in 61% vs. 38%, p = 0.049) and a higher amputation rate (20% vs. 7%, p = 0.006) when compared with those undergoing initial definitive vascular repair. CONCLUSION: Lack of TIVS was associated with a significant increase in the development of compartment syndrome. Though it seems to have become common practice to proceed directly to vascular repair during the initial surgery, morbidity is improved with the placement of a TIVS. LEVEL OF EVIDENCE: Therapeutic cohort, level III.